Enhancement of biogas production via green ZnO nanoparticles: experimental results of selected herbaceous crops. Issue 2 (1st February 2021) - Hassaan, Mohamed A.; Pantaleo, Antonio; Tedone, Luigi; Elkatory, Marwa R.; Ali, Rehab M.; Nemr, Ahmed El; Mastro, Giuseppe De
Abstract: The key to bio-gasification is the lignocellulosic materials provided in the herbaceous crops which are considered to be renewable energy resources. This study focuses on pretreatments of five selected biomass (barley, durum wheat, Abyssinian cabbage, rapeseed, and triticale) to be utilized for biogas production using chemical and green ZnO nanoparticles which were synthesized from durum wheat extract. The experimental tests were carried out to compare the different anaerobic digestion (AD) conversion efficiency with and without ZnO nanoparticles treatment on the biogas production yield. The total solids (TS), volatile solids (VS), ash content, carbon (C), hydrogen (H), and nitrogen (N) content of the tested biomass have been measured. The results revealed that durum wheat has the highest biogas yield of 353 mL/g VS compared with control biomass which produced only 271 mL/g VS. The highest specific biogas production was attained when the durum wheat was treated with 10 mg/L of chemical and green ZnO nanoparticles which produced 422 mL/g VS and 457 mL/g VS respectively compared with the control that produced only 353 mL/g VS. All results have a significant level of p < 0.05. Graphical Abstract: Schematic diagram of the biogas production from durum wheat.